Do I like my ICON? Determining preferences for firms' mode of strategic focus. (5th December 2006) - Pitt, Leyland F.; Berthon, Pierre; Prinsloo, Melani; Nel, Deon
Whether they intend to or not, firms adopt a strategic mode of focus, a way of directing efforts towards markets, products, both or neither. However, in a fast changing environment, such as South Africa, little information exists on whether managers within these organisations feel that the archetype they have adopted will be appropriate for survival in the near mid-term future. This paper reports on the results of a study that identified the modes of focus of South African firms as perceived by senior marketing managers. It then matches these to the strategic mode that the managers see as most likely to guarantee the future success of their firms. Limitations of the study are identified, implications for management highlighted and avenues for future research discussed.